Drivers of longitudinal telomere dynamics in a long‐lived bat species, Myotis myotis. Issue 16 (19th March 2020) - Foley, Nicole M.; Petit, Eric J.; Brazier, Thomas; Finarelli, John A.; Hughes, Graham M.; Touzalin, Frédéric; Puechmaille, Sébastien J.; Teeling, Emma C.
Abstract: Age‐related telomere shortening is considered a hallmark of the ageing process. However, a recent cross‐sectional ageing study of relative telomere length (rTL) in bats failed to detect a relationship between rTL and age in the long‐lived genus Myotis ( M. myotis and M. bechsteinii ), suggesting some other factors are responsible for driving telomere dynamics in these species. Here, we test if longitudinal rTL data show signatures of age‐associated telomere attrition in M. myotis and differentiate which intrinsic or extrinsic factors are likely to drive telomere length dynamics. Using quantitative polymerase chain reaction, rTL was measured in 504 samples from a marked population, from Brittany, France, captured between 2013 and 2016. These represent 174 individuals with an age range of 0 to 7+ years. We find no significant relationship between rTL and age ( p  = .762), but demonstrate that within‐individual rTL is highly variable from year to year. To investigate the heritability of rTL, a population pedigree ( n  = 1744) was constructed from genotype data generated from a 16‐microsatellite multiplex, designed from an initial, low‐coverage, Illumina genome for M. myotis . Heritability was estimated in a Bayesian, mixed model framework, and showed that little of the observed variance in rTL is heritable ( h 2  = 0.01–0.06). Rather, correlations of first differences, correlating yearly changes in telomere length and weather variables, demonstrate that, during the spring transition, average temperature, minimum temperature, rainfall and windspeed correlate with changes in longitudinal telomere dynamics. As such, rTL may represent a useful biomarker to quantify the physiological impact of various environmental stressors in bats. Abstract : see also the Perspective by Luise A. Seeker.